Prevalence and clinical profile of mycoplasma pneumoniae respiratory infection in children: a hospital based study - Cherian, Carol Sara; Nair, Thushara S.; S., Sushama Bai; Oommen, Seema (International Journal of Contemporary Pediatrics, 2016)
Background: Mycoplasma pneumoniae (M. pneum) is a well-established cause of respiratory tract infections in the pediatric population worldwide. This study aimed to assess the prevalence and clinical profile of children with mycoplasma respiratory infection. Methods: Design was prospective study. Departments of Pediatrics and Microbiology of Tertiary care Medical College. Study period was one year (Jan 2012 to Dec 2012). Children (age 3 months to 15 yrs) with respiratory tract infection symptoms of >5 days. Histories, physical examination, routine lab investigations of respiratory infection, IgM ELISA for Mycoplasma pneumoniae (M. pneum) were done. Treatment Initiated as per ARI guidelines with appropriate modifications. M. peum cases were additionally treated with azithromycin. Response assessed clinically and by investigations. Statistical analysis was done by chi-square and t-tests. Results: Prevalence of M. pneum. respiratory infection was 22.44%. Clustering of positive cases was during the pre-monsoon and monsoon seasons. Fever, sore throat and consolidation revealed significant association with M pneu-infection clinically. High ESR and absence of leucko cytosis were the significant lab parameters of M. pneum positive cases. All positive cases responded to arithromycin. There was no mortality. Conclusions: M. pneum contributes to 22.44% respiratory infections in hospital attending children. Fever, sore throat consolidation and high ESR are the significant suggestive parameters.